(untitled) (MAUSAM, 1964)
Thunderclouds constitute one of the worst hazards of flying. Over India, Cumulonimbus (Cb) clouds develop to very great heights during the southwest monsoon season, June to September. These are often embedded in other cloud layers and pose a serious problem to aviators. All available data regarding Cb clouds obtained by the meteorological reconnaissance flights and scheduled civil flights by jet aircraft across India during the last six monsoon seasons have been analysed. The mean heights of tops of Cb clouds and their diurnal and regional variations have been studied. Heights of bases of Cb clouds and weather phenomena in their vicinity are briefly discussed. Three typical Synoptic situations illustrative of thunder activity in the monsoon season aloe also described.